Medidores de energia elétrica aplicados em instalações de baixa tensão – aspectos relacionados à qualidade da energia elétrica - Souza, Pedro Mendes de (Universidade Federal de São Carlos, 2025)
This study evaluates the quality of electrical energy in low-voltage installations through the analysis of smart meters, with an emphasis on voltage imbalances and low power factor. The research considers ANEEL regulations, the technological evolution of meters, and their effectiveness in detecting anomalies. Data collection was performed using the JE05 WATT METER (BIN Technology) smart meter in a two-phase configuration, monitoring parameters such as RMS voltage, frequency, active and reactive power, and power factor over seven days, with subsequent analysis conducted in MATLAB software. The results demonstrate the superiority of smart meters in identifying critical failures, such as voltages outside regulatory standards and low power factor.
Electricity meters applied to low-voltage installations - aspects related to power quality
Keywords: Qualidade da energia elétrica; Medidores; Baixa tensão; Power quality; Meters; Low voltge; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO